Pengaruh Tingkat Kekristalan Material Grafena Oksida Tereduksi Terhadap Nilai Kuat Tekan Beton Normal - nuraini, umi; Rahayu Pradita; Qurrotus Shofiyah; Mohammad Dani Al Qori; dedi (SPECTA Journal of Technology, 2023)
Reduced graphene oxide (rGO) phase from coconut shell charcoal through heating using either a furnace or an artificial burner has been successfully formed. Heating was carried out through 2 temperature variations, namely 500 and 1000ᵒC, with a holding time of 5 hours. Heating through an artificial burner is carried out using used fuel oil equipped with a thermostat to measure the temperature. Phase identification was carried out using Xrays Diffraction Spectroscopy (XRD) testing with an angle of 2θ, namely 15-50ᵒ. The diffraction pattern shows that all samples have rGO phases with different intensity values. The higher the temperature, the greater the intensity value compared to the other samples. This intensity value indicates an increase in the sample's crystallinity due to an increase in temperature.